Pemetaan Tren: Analisis Bibliometrik dari Audit Report Lag yang Terindex Google Schoolar - Aisyah Kamila Putri; Sri Andriani; Ahmad Fahrudin Alamsyah (Yayasan Pendidikan Penelitian Pengabdian Algero, 2024)
Financial reports are an important thing that is really needed by a company. The audit assessment has an impact on the financial reports that will be published. The study of audit delays is experiencing rapid growth. This has attracted the interest of many researchers to continue developing it, including analyzing internal and external company factors that influence audit delays. However, until now, publications related to this topic have not been well organized. This research aims to map research publications related to audit delays in a database context, with the keyword